Insights Into the Genetic Diversity of Nordic Red Clover (Trifolium pratense) Revealed by SeqSNP-Based Genic Markers - Osterman, Johanna; Hammenhag, Cecilia; Ortiz, Rodomiro; Geleta, Mulatu (Frontiers in Plant Science, 2021)
Red clover (Trifolium pratense) is one of the most important fodder crops worldwide. The knowledge of genetic diversity among red clover populations, however, is under development. This study provides insights into its genetic diversity, using single nucleotide polymorphism (SNP) markers to define population structure in wild and cultivated red clover. Twenty-nine accessions representing the genetic resources available at NordGen (the Nordic gene bank) and Lantmännen (a Swedish agricultural company with a red clover breeding program) were used for this study. Genotyping was performed via SeqSNP, a targeted genotype by sequencing method that offers the capability to target specific single nucleotide polymorphism (SNP) loci and enables de novo discovery of new SNPs. The SNPs were identified through a SNP mining approach based on coding sequences of red clover genes known for their involvement in development and stress responses. After filtering the genotypic data using various criteria, 623 bi-allelic SNPs, including 327 originally targeted and 296 de novo discovered SNPs were used for population genetics analyses. Seventy-one of the SNP loci were under selection considering both Hardy-Weinberg equilibrium and pairwise FST distributions. The average observed heterozygosity (HO), within population diversity (HS) and overall diversity (HT) were 0.22, 0.21 and 0.22, respectively. The tetraploids had higher average HO (0.35) than diploids (0.21). The analysis of molecular variance (AMOVA) showed low but significant variation among accessions (5.4 %; P < 0.001), and among diploids and tetraploids (1.08%; P = 0.02). This study revealed a low mean inbreeding coefficient (FIS = -0.04) exhibiting the strict outcrossing nature of red clover. As per cluster, principal coordinate and discriminant analyses, most wild populations were grouped together and were clearly differentiated from the cultivated types. The cultivated types of red clover had a similar level of genetic diversity, suggesting that modern red clover breeding programs did not negatively affect genetic diversity or population structure. Hence, the breeding material used by Lantmännen represents the major genetic resources in Scandinavia. This knowledge of how different types of red clover accessions relate to each other and the level of outcrossing and heterozygosity will be useful for future red clover breeding.